Culture‐dependent and culture‐independent analyses reveal no prokaryotic community shifts or recovery of Serratia marcescens in Acropora palmata with white pox disease. Issue 3 (24th March 2014) - Lesser, Michael P.; Jarett, Jessica K.
Abstract Recently, the etiological agent of white pox (WP) disease, also known as acroporid serratiosis, in the endangered coral Acropora palmata is the enteric bacterium Serratia marcescens with the source being localized sewage release onto coastal coral reef communities. Here, we show that both culture‐dependent and culture‐independent approaches could not recover this bacterium from samples of tissue and mucus from A. palmata colonies affected by WP disease in the Bahamas, or seawater collected adjacent to A. palmata colonies. Additionally, a metagenetic 16S rRNA pyrosequencing study shows no significant difference in the bacterial communities of coral tissues with and without WP lesions. As recent studies have shown for other coral diseases, S. marcescens cannot be identified in all cases of WP disease in several geographically separated populations of A. palmata with the same set of signs. As a result, its identification as the etiological agent of WP disease, and cause of a reverse zoonosis, cannot be broadly supported. However, the prevalence of WP disease associated with S. marcescens does appear to be associated with proximity to population centers, and research efforts should be broadened to examine this association, and to identify other causes of this syndrome.